Thai Indigenous Lowland Rice Germplasms: Sources of Bacterial Blight Disease Resistance and Agronomic Attributes - Menson R. Kwanwah; Tanawat Wongsa; Tidarat Monkham; Sompong Chankaew; Shanerin Falab; Jirawat Sanitchon (AGRIVITA, Journal of Agricultural Science, 2020)
Bacterial blight (BB) has caused significant reductions in yield and quality of rice. The use of genetically resistant cultivars has proven to be one of the most effective methods used to address this problem. This study screened a total of 333 Thai lowland indigenous rice germplasms against four Xanthomonas oryzae pv. oryzae (Xoo) isolates under greenhouse conditions in the rainy and dry seasons of 2017. The ten varieties demonstrating the greatest BB resistance in the lower five centimeters of the lesion lengths in both experiment years were further investigated and validated for their agronomic performances in field conditions at the Udon Thani Rice Research Center in 2018. Our findings revealed that of the ten BB resistant lowland rice varieties, five varieties; LLR023, LLR134, LLR137, LLR205 and LLR207, exhibited high performances of agronomic traits in field conditions; as found in the plant height, tiller number, panicle number, panicle length, seeds per panicle, grain yield and harvest index when compared with the KDML105 check varieties. These five selected rice varieties may further serve as new genetic resources for future BB resistance and agronomic trait improvement programs.